2022
DOI: 10.3389/fmicb.2022.997849
|View full text |Cite
|
Sign up to set email alerts
|

Conjugative transfer of multi-drug resistance IncN plasmids from environmental waterborne bacteria to Escherichia coli

Abstract: Watersheds contaminated with municipal, hospital, and agricultural residues are recognized as reservoirs for bacteria carrying antibiotic resistance genes (ARGs). The objective of this study was to determine the potential of environmental bacterial communities from the highly contaminated La Paz River basin in Bolivia to transfer ARGs to an Escherichia coli lab strain used as the recipient. Additionally, we tested ZnSO4 and CuSO4 at sub-inhibitory concentrations as stressors and analyzed transfer frequencies (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Firstly, the incompatibility group IncN is very abundant in wastewater of human origin, both municipal and hospital sources. In a study conducted in the La Paz River basin in Bolivia, where hospitals, industries, and households discharge directly, all the plasmids detected from the urban site were IncN (Guzman-Otazo et al 2022 ). A comparative study of the inlet of a municipal wastewater treatment plant (WWTP) and the main sewer line of a Swedish hospital also revealed that IncN plasmids constituted the majority of the microbial population (Hutinel et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the incompatibility group IncN is very abundant in wastewater of human origin, both municipal and hospital sources. In a study conducted in the La Paz River basin in Bolivia, where hospitals, industries, and households discharge directly, all the plasmids detected from the urban site were IncN (Guzman-Otazo et al 2022 ). A comparative study of the inlet of a municipal wastewater treatment plant (WWTP) and the main sewer line of a Swedish hospital also revealed that IncN plasmids constituted the majority of the microbial population (Hutinel et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ST410 isolates described in this study were not MDR, but carried the CS23 operon in combination with LT and STh. A study that has assessed the transfer of multidrug resistance plasmid from Choqueyapu’s waterborne bacteria to E. coli indicated that the IncN plasmid carrying a wide range of ARGs and intl1 were transferred with high frequency (61). A potentially dangerous scenario is in which virulence genes and last-generation MDR genes are combined in one ST410 isolate.…”
Section: Discussionmentioning
confidence: 99%
“…[ 300 ]), and although some treatment processes can efficiently remove AR [ 301 ], they are seldom used, especially in poor countries, whileothers can actually select for AR [ 302 ]. By putting together pathogens, commensals and environmental bacteria, AR and mobility genes, and selective pressures favoring AR, WW is an ideal environment for the emergence of mobile AR genes that can then be spread into different bacteria, including pathogens [ 303 , 304 ]. AR genes that enter the environment, mostly onboard bacteria from humans and animals, are then transferred horizontally, as they are commonly linked to mobile elements [ 305 ].…”
Section: Non-canonical Dispersion Of Armentioning
confidence: 99%